What Does The Existential-Phenomenological Approach Have To Offer The Current Understanding Of The Pre-Verbal Months Of An Infant? (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
This paper looks at whether an exploration of the pre-verbal months of an infant might be better served by appealing to the arts, and more specifically to a phenomenological approach equipped to take into account the intersubjective feel of an infant's world, than to the hitherto dominant realm of the sciences and developmental stage theory.
Keywords: Pre-verbal infant; developmental stage theory; accommodating ambiguity; the 'clinical infant'; mother-baby relationship; self; differentiation; non-self-reflexive mirroring